2017
DOI: 10.1016/j.jhe.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Household wealth in the euro area: The importance of intergenerational transfers, homeownership and house price dynamics

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Of course the self-reported values might not reflect the actual market values. However, a comparison between values declared in SHARE Wave 4 and in the Eurosystem Household Finance and Consumption Survey for the same year shows only minor differences, although the latter are systematically higher (a similar evidence is also reported in Mathä et al 2014 Only three countries show a percentage higher than 15: Sweden, the Netherlands and Denmark. One of the reasons for the three exceptions may be the existence of mortgage formulae that allow the beneficiary to repay only the interest, thus leaving the debt and the house to the offspring.…”
Section: Homeownership Across European Countriessupporting
confidence: 69%
“…Of course the self-reported values might not reflect the actual market values. However, a comparison between values declared in SHARE Wave 4 and in the Eurosystem Household Finance and Consumption Survey for the same year shows only minor differences, although the latter are systematically higher (a similar evidence is also reported in Mathä et al 2014 Only three countries show a percentage higher than 15: Sweden, the Netherlands and Denmark. One of the reasons for the three exceptions may be the existence of mortgage formulae that allow the beneficiary to repay only the interest, thus leaving the debt and the house to the offspring.…”
Section: Homeownership Across European Countriessupporting
confidence: 69%
“…For instance, it is suggested that owner-occupied homes tend to be larger, of better quality and situated in generally more attractive residential environments (Megbolugbe & Linneman, 1993;Mulder et al, 2006;Mulder & Wagner, 1998). From a financial perspective, the purchase of a home can be an attractive and relatively safe long-term investment, particularly in countries that actively promote homeownership with subsidies and tax incentives (Matha et al, 2014). However, as briefly mentioned above, the initial financial costs, including for instance transaction charges and transfer taxes, as well as any ongoing costs associated with the repayment of mortgages and the maintenance of the dwelling, are all burdens to which renters are largely immune.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Moreover, they have been employed to compare differences in income distributions across regions (Nguyen et al 2007) as well as across countries (e.g., Blau and Kahn 1996). Following the recent availability of microsurveys with information on household balance sheets, decomposition methods have also been used to perform comparisons in household finances across time or countries (see, e.g., Gale and Pence 2006, Bover 2010, Sierminska and Doorley 2012, Christelis, Georgarakos, and Haliassos 2013, Mathä, Porpiglia, and Ziegelmeyer 2017.…”
Section: Decomposition Methodologymentioning
confidence: 99%
“…They conclude that the importance of household characteristics in determining differences in several assets and debts varies by age. Finally, Mathä, Porpiglia, and Ziegelmeyer (2017) use more recent cross‐country survey data that are fully harmonized to examine the importance of intergenerational transfers, home ownership, and house price dynamics for wealth differences in the euro area.…”
mentioning
confidence: 99%